2018
DOI: 10.1002/gcc.22523
|View full text |Cite
|
Sign up to set email alerts
|

Multiple DICER1‐related tumors in a child with a large interstitial 14q32 deletion

Abstract: Germ-line interstitial deletions involving the 14q32 chromosomal region, resulting in 14q32 deletion syndrome, are rare. DICER1 is a recently described cancer-predisposition gene located at 14q32.13. We report the case of a male child with a ∼5.8 Mbp 14q32.13q32.2 germ-line deletion, which included the full DICER1 locus. We reviewed available clinical and pathological material, and conducted genetic analyses. In addition to having congenital dysmorphic features, the child developed multiple DICER1 syndrome-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Moreover, in TA3 Hauschka and C-127I, breakpoints homologous to human band 14q32 could be observed. Notably, there, the gene DICER1 is located, recently identified as playing a role in cancer predisposition [ 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in TA3 Hauschka and C-127I, breakpoints homologous to human band 14q32 could be observed. Notably, there, the gene DICER1 is located, recently identified as playing a role in cancer predisposition [ 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While most individuals with DICER1 syndrome are heterozygous for a germline loss‐of‐function DICER1 pathogenic variant, other predisposing DICER1 alterations have also been documented. These include deletion of the entire DICER1 locus (de Kock, Geoffrion, et al, ; de Kock et al, ; Herriges et al, ; van Engelen et al, ), in‐ and out‐of‐frame intragenic deletions involving one or more exons (Apellaniz‐Ruiz et al, ; Brenneman et al, ; Sabbaghian et al, ), and somatic mosaicism, which is observed in a small fraction of syndromic patients (Brenneman et al, ; de Kock et al, ; Klein et al, ). Individuals with mosaicism for loss‐of‐function mutations tend to exhibit one or two foci of disease; in contrast, mosaicism for RNase IIIb hotspot mutations results in a greater number of disease foci at significantly younger ages than is typical (Brenneman et al, ; de Kock et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with Beckwith-Wiedemann syndrome and CDKN1C mutations, an extended phenotype including ear pits and polydactyly has been described. To date, ID/developmental delay has been reported in at least nine patients with large deletions encompassing several genes including DICER1, [21][22][23][24][25][26][27] and in three patients with RNase IIIb or RNase IIIa-S1344L hotspot mutations. 5 10 The highly penetrant and severe phenotypes described in patients with germline or mosaic RNase III domain mutations 5 6 may be explained by the likelihood of a second somatic mutation stochastically occurring in any part of DICER1 being greater than the reverse succession normally seen in DICER1 syndrome, in combination with tissue-specific neomorphic effects of the specific heterozygous RNase III domain mutations.…”
Section: Discussionmentioning
confidence: 99%